Prevention and Management of Type 2 Diabetes and Metabolic Syndrome in the Time of COVID-19: Should We Add a Cup of Coffee? - Semiz, Sabina; Serdarevic, Fadila (Frontiers in Nutrition, 2020)
A recent evidence show that COVID-19 patients with existing metabolic disorders, such as diabetes and metabolic syndrome, are exposed to high risk of morbidity and mortality. At the same time, in order to manage the pandemic, the health authorities around the world are advising people to stay at home. This results in decreased physical activity and increased consumption of unhealthy diet, which often lead to increase in body weight, risk for diabetes, insulin resistance, and metabolic syndrome, and thus, paradoxically, to high risk of morbidity and mortality due to COVID-19 complications. Here we summarize the evidence demonstrating that promotion of healthy life style, including physical activity and dietary intake of natural polyphenols present in coffee and tea, has potential to improve prevention and management of insulin resistance and diabetes in the time of COVID-19 pandemic. Particularly, it would be pertinent to evaluate further the potential positive effects of coffee beverages, rich in natural polyphenols, as an adjuvant therapy for COVID-19, which appear not to be studied sufficiently.